2017
DOI: 10.1021/acscatal.7b00729
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Hydrogenation over a Metal-Free Carbon-Based Catalyst

Abstract: The hydrogenation of CO2 into useful chemicals provides an industrial-scale pathway for CO2 recycling. The lack of effective thermochemical catalysts currently precludes this process, since it is challenging to identify structures that can simultaneously exhibit high activity and selectivity for this reaction. Here, we report, for the first time, the use of nitrogen-doped graphene quantum dots (NGQDs) as metal-free catalysts for CO2 hydrogenation. The nitrogen dopants, located at the edge sites, play a key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 33 publications
6
44
0
2
Order By: Relevance
“…This fact is in good accordance with the expectations based on molecular chemistry that shows that while pyridine is a base, pyrrole and quaternary N are much less or not basic. These results are also in agreement with the proposal of Wu and coworkers that have suggested pyridinic N atoms at the periphery of graphene dots as the active sites of CO 2 hydrogenation in these materials …”
Section: Defective Graphenes Studied As Sabatier Catalysts With Indicsupporting
confidence: 93%
See 1 more Smart Citation
“…This fact is in good accordance with the expectations based on molecular chemistry that shows that while pyridine is a base, pyrrole and quaternary N are much less or not basic. These results are also in agreement with the proposal of Wu and coworkers that have suggested pyridinic N atoms at the periphery of graphene dots as the active sites of CO 2 hydrogenation in these materials …”
Section: Defective Graphenes Studied As Sabatier Catalysts With Indicsupporting
confidence: 93%
“…Although graphenes have been reported to exhibiting catalytic hydrogenation activity for alkenes, it is important if they are also able to promote hydrogenation of more stable molecules, such as CO 2 , determining their activity and product selectivity. In a recent precedent, it has been found that N‐doped graphene quantum dots are catalytically active for CO 2 hydrogenation to CO or CH 4 due to the presence of pyridinic N atoms at the periphery of the dots . The present study reaches similar conclusions, but shows that nanometric dimension is not a prerequisite and that larger micrometric defective graphene ( d G ) sheets, even with other dopant heteroatoms, exhibit similar behavior as CO 2 methanation catalyst.…”
Section: Defective Graphenes Studied As Sabatier Catalysts With Indicsupporting
confidence: 85%
“…Furthermore, the local electric filed between positively charged Au + and coordinated N with high electron cloud density enables the photogenerated electrons to transfer to Au + , thus inhibiting the recombination‐rate of carriers (Figures S11 and S12 in the Supporting Information) and increasing the lifetime of carriers (Figure S13 in the Supporting Information). CO 2 is adsorbed on Lewis basic N and urea‐introduced amino groups; therefore, the CO 2 reduction process takes place in two paths (Figure ): i) CO 2 adsorbs on Lewis basic N site (around Au + ), is reduced by the electrons on Au + . Moreover, the lower energy barrier of adsorbed intermediates around single Au atoms favors the eight‐electron path, thus increasing the CH 4 production.…”
Section: Figuresupporting
confidence: 78%
“…However, it is difficult to directly break the C=O bond in the aldehyde group, suggesting the presence of another intermediate reaction. In the process of CO 2 reduction on Pt 1 /graphitic carbon nitride, the dissociation of CH 2 OH* to CH 2 * is the intermediate reaction of CH 4 production, and CH 2 OH* is the intermediate of CO 2 reduction to CH 4 on carbon‐based catalyst, suggesting that the next reduction product of HCHO* is CH 2 OH*. The subsequent hydrogenation of CH 2 * to CH 4 can easily happen .…”
Section: Figurementioning
confidence: 90%
“…A typical cobalt catalyst for CO 2 hydrogenation consists of supported cobalt nanoparticles on the order of 5–15 nm . However, at the nanoscale a high degree of heterogeneity is found on the catalytically relevant surface structures, arising from changes in particle size, surface crystal faceting, or point defects . Studies performed on single crystal surfaces in ultra‐high vacuum conditions mitigate the heterogeneity of the active sites by rigorously characterizing the surface, however, such degree of characterization is not feasible on powder catalysts at the 5–10 nm scale.…”
Section: Introductionmentioning
confidence: 99%